Reaction microscope endstation at FLASH2 - Schmid, Georg (Journal of synchrotron radiation, 2019)
A reaction microscope dedicated to multi-particle coincidence spectroscopy on gas-phase samples is installed at beamline FL26 of the free-electron laser FLASH2 in Hamburg. The main goals of the instrument are to follow the dynamics of atoms, molecules and small clusters on their natural time-scale and to study non-linear light-matter interaction with such systems. To this end, the reaction microscope is combined with an in-line extreme-ultraviolet (XUV) split-delay and focusing optics, which allows time-resolved XUV-XUV pump-probe spectroscopy to be performed